Instrumentation for the operating room : a photographic manual - Tighe, Shirley M. (London, United Kingdom : Elsevier Health Sciences, 2012)
With more than 1,000 photographs of surgical instruments and instrument tips in the book and online, Instrumentation for the Operating Room: A Photographic Manual, 8th Edition, shows more illustrations than any other manual. Instruments are organized by surgical specialty, beginning with basic sets and progressing to more advanced sets. Instructions on preparation, sterilization, and setup, as well as clear explanations for common surgical procedures can be found throughout the book.
Instrument Preparation for Surgery -- General Surgery -- Female Reproductive Surgery -- Genitourinary Surgery -- Orthopedic surgery -- Eye, ear, nose, and throat surgery -- Oral, maxillary, and facial surgery -- Plastic surgery -- Peripheral vascular, cardiovascular, and thoracic surgery -- Pediatric surgery -- Neurosurgery
Includes bibliographical references and index.
Keywords: SURGICAL INSTRUMENTS AND APPARATUS